Factors Influencing the Crystallization-Onset Time of Metastable ASDs - Friederike Wolbert; Ineke-Katharina Fahrig; Tobias Gottschalk; Christian Luebbert; Markus Thommes; Gabriele Sadowski (MDPI AG, 2022)
In formulation development, amorphous solid dispersions (ASD) are considered to improve the bioavailability of poorly water-soluble active pharmaceutical ingredients (APIs). However, the crystallization of APIs often limits long-term stability and thus the shelf life of ASDs. It has already been shown earlier that the long-term stability of ASDs strongly depends on the storage conditions (relative humidity, temperature), the manufacturing methods, and the resulting particle sizes. In this work, ASDs composed of the model APIs Griseofulvin (GRI) or Itraconazole (ITR) and the polymers poly (vinylpyrrolidone-co-vinyl acetate) (PVPVA) or Soluplus® were manufactured via spray drying and hot-melt extrusion. Each API/polymer combination was manufactured using the two manufacturing methods with at least two different API loads and two particle-size distributions. It was a priori known that these ASDs were metastable and would crystallize over time, even in the dry stage. The amount of water absorbed by the ASD from humid air (40 °C/75% relative humidity), the solubility of the API in the ASD at humid conditions, and the resulting glass-transition temperature were predicted using the Perturbed-Chain Statistical Associating Fluid Theory (PC-SAFT) and the Gordon-Taylor approach, respectively. The onset of crystallization was determined via periodic powder X-ray diffraction (PXRD) measurements. It was shown that simple heuristics such as "larger particles always crystallize later than smaller particles" are correct within one manufacturing method but cannot be transferred from one manufacturing method to another. Moreover, amorphous phase separation in the ASDs was shown to also influence their crystallization kinetics. Counterintuitively, phase separation accelerated the crystallization time, which could be explained by the glass-transition temperatures of the evolving phases.